Forgiveness mahasiswa ditinjau dari dukungan sosial - Inge V. A. Nalle; Husnul Khotimah (Jurnal Psikologi Tabularasa, 2020)
An interpersonal relation have a high risk for causing a heartbreak within every person involved. Forgiving is one of the key of heartbreak remedies. However, it requires a great inside power to be able to forgive the others, that power would be even greater with the social support. This research aims to find relationship between social support towards forgiving behavior of college students. There are 420 college students involved as the sample of this quantitative research. Data retrieval uses a forgive behavior scale and a social support scale. Analysis correlation test prove that there is a relation between the social supports and student's forgiving behavior.